Strategi Pengurus Masjid dalam Memakmurkan Masjid Al-Furqon di Haurgeulis Indramayu - Suhariyanti Suhariyanti; Sobirin Sobirin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
To prosper the mosque requires a good strategy, with a good strategy the program of mosque activities can run effectively and efficiently to achieve the goal of broadcasting Islam and its prosperity. The purpose of the study was to find out how the mosque management strategy in prospering the Al-Furqon mosque in Haurgeulis Indramayu. This research is a field research. This study uses a qualitative research method, with a literature and empirical approach, interview data collection techniques, observation and documentation. The results of the research on the strategies used by mosque administrators in prospering the Al-Furqon Mosque are using socialization strategies for the congregation through a door-to-door approach, and social programs for the congregation so that the congregation can be directed to participate in activities held in the congregation. Al-Furqon Mosque.Keywords: Strategy; Mosque Management; Prospering Mosque. AbstrakUntuk memakmurkan masjid memerlukan strategi yang baik, dengan strategi yang baik program kegiatan masjid dapat berjalan efektif dan efisien untuk mencapai tujuan dalam menyiarkan Islam dan kemakmurannya. Tujuan penelitian untuk mengetahui bagaimana strategi pengurus masjid dalam memakmurkan masjid Al-Furqon di Haurgeulis Indramayu. Penelitian ini menggunakan metode penelitian Kualitatif, dengan pendekatan literatur dan empiris, teknik pengumpulan data wawancara, observasi dan dokumentasi. Hasil penelitian strategi yang digunakan oleh pengurus masjid dalam memakmurkan Masjid Al-Furqon adalah menggunakan strategi sosialisasi pada jama’ah melalui pendekatan dari rumah ke rumah, dan program sosial terhadap jama’ah sehingga jama’ah dapat diarahkan untuk mengikuti kegiatan-kegiatan yang diadakan di masjid Al-Furqon.Kata Kunci: Strategi; Pengurus Masjid; Memakmurkan Masjid